2015
DOI: 10.2147/ijn.s91579
|View full text |Cite
|
Sign up to set email alerts
|

Novel platinum–palladium bimetallic nanoparticles synthesized by Dioscorea bulbifera: anticancer and antioxidant activities

Abstract: Medicinal plants serve as rich sources of diverse bioactive phytochemicals that might even take part in bioreduction and stabilization of phytogenic nanoparticles with immense therapeutic properties. Herein, we report for the first time the rapid efficient synthesis of novel platinum–palladium bimetallic nanoparticles (Pt–PdNPs) along with individual platinum (PtNPs) and palladium (PdNPs) nanoparticles using a medicinal plant, Dioscorea bulbifera tuber extract (DBTE). High-resolution tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 41 publications
6
20
0
Order By: Relevance
“…Hereby, herbal extracts rich in diverse groups of phytochemicals is preferred for simultaneous synthesis and capping of metal nanoparticles [8,9]. Medicinal plants like Dioscorea bulbifera, Dioscorea opposiifolia, Barleria prionitis, Gloriosa superba, Gnidia glauca, Plumbago zeylanica, have exhibited their nanobiotechnological potential towards synthesis of gold, silver, copper, platinum and palladium nanoparticles with biological activities [10][11][12][13][14][15][16][17][18][19]. Earlier reports showed that the phytogenic nanoparticles were more biocompatible and bioactive as compared to the chemically synthesized nanoparticles [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, herbal extracts rich in diverse groups of phytochemicals is preferred for simultaneous synthesis and capping of metal nanoparticles [8,9]. Medicinal plants like Dioscorea bulbifera, Dioscorea opposiifolia, Barleria prionitis, Gloriosa superba, Gnidia glauca, Plumbago zeylanica, have exhibited their nanobiotechnological potential towards synthesis of gold, silver, copper, platinum and palladium nanoparticles with biological activities [10][11][12][13][14][15][16][17][18][19]. Earlier reports showed that the phytogenic nanoparticles were more biocompatible and bioactive as compared to the chemically synthesized nanoparticles [13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, GSTE before bioreduction was also used to compare the alteration of the phytochemistry. The KBr pellet containing GSTE before and after bioreduction was subjected to FTIR (IRAffinity-1, Shimadzu Corp, Tokyo, Japan) spectroscopy measurement in the diffused reflection mode at a resolution of 4 cm −1 subjected to the IR source 500–4000 cm −1 [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…5 × 10 5 cells were initially seeded in a T-25 flask and incubated for 24 hours followed by addition of PtNPs and PdNPs nanoparticles at a concentration of 200 µ g/mL. After 48 hours of incubation, the cells were harvested and stained with Annexin V-FITC (dilution 1 : 20) and propidium iodide (dilution 1 : 20) for 15 minutes at 4°C and were acquired using BD FACSVerse and analyzed by BD FACSuit software as reported earlier [ 8 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…A careful study of the toxicological profile and intracellular fate of NPs is crucial to uncover their biomedical potential [28,31,33]. Although there are several studies reported in the literature [1,9,10,13,14,[19][20][21][22][23][24][25][26][27][48][49][50][51][52][53][54], there is a lack of conclusive data about the biocompatibility of PdNPs. The results are rather conflicting, likely due to the high variety of PdNP synthetic protocols, dimensions, shapes, surface capping agents, purity, cellular lines used for toxicity tests, and the variability of experimental conditions.…”
Section: Toxicity Assessment Of Pdnpsmentioning
confidence: 99%
“…Preliminary data suggest that PdNPs possess radical scavenging activity similar to that of natural enzymes, namely catalase (CAT) [14,16], peroxidase (HRP) [3,16,17], and superoxide dismutase (SOD) [14,15], but these studies are limited to a few cases, in a cell-free environment, and do not provide a clear picture of their structure-function relationship [18]. Moreover, despite such interesting features, the biomedical use of PdNPs is still limited, partially due to conflicting data about their toxicity [19][20][21][22][23][24][25][26][27]. In this regard, the presence of synthesis by-products, endotoxins, contaminations, and surface functionalities has a strong influence and could be the reason of the observed toxicity in many reports [28].…”
Section: Introductionmentioning
confidence: 99%